Workplace health promotion in the context of public health (Italian Journal of Public Health, 2010)
In modern societies, work is the source of most individual, corporate and community wealth. The level ofeach society’s health is therefore particularly vulnerable to disruption caused by employee illness. Todayhealthy workplaces are one of the most important determinants of health. However, public health has tendedto completely ignore health in the workplace and occupational medicine has tended to ignore it in part. Thisarticle refers to the Italian and European context and, through a review of international recommendations,research and direct field experiences, presents workplace health promotion as an important tool in the fieldof public health.Through the years, several initiatives have been tested. One of the platforms that has demonstrated to becost effective is based on the principles included in the Ottawa Charter which, when applied to the workplace,define workplace health promotion. In the last twelve years, the European Commission has recognized theworkplace as a key determinant of health and has outlined a methodology of workplace health promotion asdefined in the Luxemburg Declaration. The basis of this methodology is planning. Without correct strategyand policy development it will not be possible to create a sustainable society. The enforcement of Lisbontreaty seems to be a substantial step forward for Europe.
Keywords: health; safety; workplace; public health; workplace health promotion